Echogenic Glycol Chitosan Nanoparticles for Ultrasound-Triggered Cancer Theranostics - Min, Hyun Su; You, Dong Gil; Son, Sejin; Jeon, Sangmin; Park, Jae Hyung; Lee, Seulki; Kwon, Ick Chan; Kim, Kwangmeyung (IVYSPRING INT PUBL, 2015)
Theranostic nanoparticles hold great promise for simultaneous diagnosis of diseases, targeted drug delivery with minimal toxicity, and monitoring of therapeutic efficacy. However, one of the current challenges in developing theranostic nanoparticles is enhancing the tumor-specific targeting of both imaging probes and anticancer agents. Herein, we report the development of tumor-homing echogenic glycol chitosan-based nanoparticles (Echo-CNPs) that concurrently execute cancer- targeted ultrasound (US) imaging and US-triggered drug delivery. To construct this novel Echo-CNPs, an anticancer drug and bioinert perfluoropentane (PFP), a US gas precursor, were simultaneously encapsulated into glycol chitosan nanoparticles using the oil in water (O/W) emulsion method. The resulting Echo-CNPs had a nano-sized particle structure, composing of hydrophobic anticancer drug/PFP inner cores and a hydrophilic glycol chitosan polymer outer shell. The Echo-CNPs had a favorable hydrodynamic size of 432 nm, which is entirely different from the micro-sized core-empty conventional microbubbles (1-10 mu m). Furthermore, Echo-CNPs showed the prolonged echogenicity via the sustained microbubble formation process of liquid-phase PFP at the body temperature and they also presented a US-triggered drug release profile through the external US irradiation. Interestingly, Echo-CNPs exhibited significantly increased tumor-homing ability with lower non-specific uptake by other tissues in tumor-bearing mice through the nanoparticle's enhanced permeation and retention (EPR) effect. Conclusively, theranostic Echo-CNPs are highly useful for simultaneous cancer-targeting US imaging and US-triggered delivery in cancer theranostics.
Keywords: TARGETED MICROBUBBLE DESTRUCTION; DRUG-DELIVERY; MULTIFUNCTIONAL NANOPARTICLES; CONTROLLED-RELEASE; GENE; MODALITY; EFFICACY; PROGRESS